The market approach to valuing bussinesses - Pratt, Shannon P. (John Wiley & Son, 2006)
An essential guide for anyone who owns a small or large business, a professional practice, or a partial interest, The Market Approach to Valuing Businesses covers applications including: pricing for purchases and sales , marital dissolution property valuation, valuation for gift and estate taxes, shareholder matters, such as dissenting stockholder suits, minority oppression actions, and resolutions of value under buy-sell agreements.